34‐3: OLED Display with High Resolution Fabricated by Electrohydrodynamic Printing. Issue 1 (25th September 2020) - Mu, Lan; Jiang, Congbiao; Wang, Juanhong; Zheng, Hua; Ying, Lei; Xu, Miao; Wang, Jian; Peng, Junbiao; Cao, Yong
Abstract : A super high‐resolution OLED display has been fabricated via electrohydrodynamic printing. The solvent properties dominate the ink's printability and printing stability. By using a 1.5 µm diameter nozzle, the line widths of printed polymers are reduced to less than 2 µm. A green‐color passive matrix display with a resolution of 2115 PP1 (pixel per inch) has been successfully realized.